From academic heritage to Aboriginal priorities: Anthropological responsibilities - Glowczewski, Barbara (Revista de Antropologia da UFSCar, 2012)
Throughout my 34 years of involvement with aboriginal people across australia, I have regularly chosen to respond to aboriginal priorities against a certain academic heritage, illustrated by the refusal of some colleagues – in France or Australia – to recognise the importance of women’s agency in the society, the impact of history on aboriginal ritual life and cosmology, the continuity of their culture in new forms of creativity, the respect of ethical protocols, the discrimination and social injustice suffered by indigenous people and the legitimacy of their political struggles.